KONSERVASI LINGKUNGAN SEBAGAI UPAYA MENCAPAI TUJUAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) DI SD NEGERI BENDAN NGISOR - Annisa Shidqi Nabila; Nugraheni, Nursiwi (Jurnal Samudra Geografi, 2025)
The current condition of the earth is carrying too much burden. There is a lot of environmental damage everywhere. This condition made many countries agree to resolve this environmental problem by agreeing on the 17 SDGs goals which were implemented on September 25 2015 at the UN forum in New York. Because environmental problems are our common problem, all levels of society are obliged to take a role. Educational institutions are no exception. This research uses a qualitative descriptive method which aims to be able to tell about phenomena or experiences that occur in a place so that we can draw conclusions from these phenomena. The results of this research show that the environmental conservation efforts carried out at Bendan Ngisor State Elementary School are very good for achieving the SDGs goals. The strategies used at Bendan Ngisor State Elementary School are: 1) grouping waste based on type; 2) implement the 3Rs; and 3) make eco enzymes from organic waste.